Daily or on-demand oral tenofovir disoproxil fumarate/emtricitabine for HIV pre-exposure prophylaxis: experience from a hospital-based clinic in France. (24th September 2018) - Noret, Marion; Balavoine, Stéphanie; Pintado, Claire; Siguier, Martin; Brun, Alexandre; Bauer, Rebecca; Loze, Bénédicte; Leplatois, Anne; Aslan, Alexandre; Moudachirou, Khafil; Delaugerre, Constance; Rozenbaum, Willy; et al.
Abstract : Background: On-demand oral tenofovir disoproxil fumarate and emtricitabine (TDF/FTC) has been approved for pre-exposure prophylaxis (PrEP) in MSM in France following the results of clinical studies, but data are limited on real-world experience. Design: A single-center, open-label, prospective cohort study that recruited people at high risk of HIV infection in Paris. Methods: Participants were enrolled in a single hospital-based outpatient clinic and were proposed to start PrEP with daily or on demand TDF/FTC. At baseline and every 3 months thereafter, patients were tested for HIV and creatinine plasma levels, and data on sexual behavior, other sexually transmitted infections (STIs), and tolerability were collected. Results: From 10 November 2015 to 30 April 2017, 1069 patients were screened and 1049 (98.1%) started PrEP. Median age was 36 years, 99.4% were MSM with a median number of partners of 10, and 793 (75.6%) opted for on demand PrEP. Over 486 person-years of follow-up, four HIV-infections were diagnosed in poorly or nonadherent patients (incidence 0.82/100 person-years). Rate of condomless sex at last intercourse increased from 53.3% at baseline to 79% at month 12 ( P < 10 −4 ), but increase in bacterial STI rates was modest (14.6% at baseline vs. 19.2% at month 12; P < 10 −4 ). Most adverse events were gastrointestinal and did not lead to PrEP discontinuation. Conclusions: Most PrEP users were high-risk MSM and opted for on-demand PrEP. PrEP use was associated with a low HIV incidence and a high rate of condomless sex with a modest increase in bacterial STIs.